A imunidade tributária do art.150, VI, b e c da Constituição Federal Brasileira de 1988 - Barrueco, Fernando Mauro (2015)
This study seeks to bring the understanding of tax immunity system according to article 150, VI, "b" and "c" of the Federal Constitution of 1988. Each type of immunity from the constitutional law is analyzed. It is also brought to light the controversy regarding the taxation of the activities of each associative type embraced by the constituent present in the Federal Constitution. Tax exemption is only possible to be dealt with before the mandatory tax jurisdiction that limits the powers of the Federal Government, the Municipalities, the States and the Federal District to create taxes. The tax treatment given to commercial exploitation and to the properties owned by the Church ("b" of article 150, VI of the Constitution of 1988), that is, revenue originating from atypical activities, has always raised doubts in jurisprudence and caused doctrine to have different views, today. It is no different the tax treatment given to production and circulation of goods from entities mentioned in article 150, VI, "c" of 1988 Federal Constitution, since the atypical activities are regarded by many as taxable. Typical activities, in turn, when related to temples of any cult, must be qualified for full immunity while entities of article 150, VI, "c" of the 1988 Federal Constitution, have to face the immunity rules of limited discretionary accountability which depends on the supplementary law. The present investigation discusses the controversy on the adoption of either ordinary or supplementary law. Courts major position is towards ratification of article 14 of the National Tax Code, as a requirement to qualify which entities should be entitled to immunity. Finally, in order no to stay only in theoretical level, this study will analyze the application of immunity to associative types of article 150 , VI, "b" and "c of the Federal Constitution 1988, from the perspective of Brazilian courts